2006
DOI: 10.1177/1091142105282598
|View full text |Cite
|
Sign up to set email alerts
|

Voting for a Lottery

Abstract: State lotteries have been adopted by thirty-eight states, primarily as a means of funding “good causes” or closing budgetary gaps. While several studies have identified the regressive nature of lotteries and factors responsible for their expansion, less is known about the underlying voting patterns that have driven this expansion. This article examines county-level voting patterns from the 2002 Tennessee lottery referendum and county-level lottery expenditures to determine whether voting reflects a latent dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
5
20
2
Order By: Relevance
“…Several studies have found that African Americans play the lottery more than whites do (Clotfelter and Cook, 1987;Borg and Mason, 1988;Rubenstein and Scafi di, 2002;Ghent and Grant, 2007). Giacopassi, Nichols, and Stitt (2006) fi nd no effect of race on total lottery sales in Tennessee, but when sales are sorted by game type, they fi nd that African Americans play signifi cantly more online games than their white counterparts.…”
Section: The Demand For Lottery Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that African Americans play the lottery more than whites do (Clotfelter and Cook, 1987;Borg and Mason, 1988;Rubenstein and Scafi di, 2002;Ghent and Grant, 2007). Giacopassi, Nichols, and Stitt (2006) fi nd no effect of race on total lottery sales in Tennessee, but when sales are sorted by game type, they fi nd that African Americans play signifi cantly more online games than their white counterparts.…”
Section: The Demand For Lottery Productsmentioning
confidence: 99%
“…HINC, households earning more than $50,000 per year, is the omitted baseline category. Similar measures have been used in Hersch and McDougall (1989), Giacopassi, Nichols, and Stitt (2006), and Ghent and Grant (2007).…”
Section: The Demand For Lottery Productsmentioning
confidence: 99%
“…Studies of lottery adoption includeFiler et al (1988),Berry and Berry (1990),Caudill et al (1995),Mixon et al (1997),Erekson et al (1999),Glickman and Painter (2004), andGiacopassi et al (2006). Many of these studies are compared in the review byCoughlin et al (2006).…”
mentioning
confidence: 98%
“…But in spatial studies of demand at the level of US counties or zip codes, while Giacopassi et al. () found the negative relationship between sales and the proportion of graduates in a county that might have been expected from household studies, Price and Novak () reported the opposite for lotto in Texas; and Oster () found that the proportion of graduates in a zip code played no role in predicting sales of Powerball. In our present results, for spatial units that aggregate many more households than in the American research, we find that education is a strongly positive predictor of sales (further, the significant positive coefficient estimate on the interaction term between education and real jackpot indicates that this relationship strengthens in higher jackpot draws).…”
Section: Resultsmentioning
confidence: 99%